PENGARUH FREKUENSI PEMBERIAN AIR TERHADAP PERTUMBUHAN BIBIT JABON MERAH (Anthocephalus macrophyllus (Roxb.) Havil) - Sukarman Hi. Jafar; Alfonsius . Thomas; Josephus I. Kalangi; Marthen T. Lasut (Universitas Sam Ratulangi, 2013)
ABSTRACTFrequency Effect on growth of seedlings water provision jabon Red (Anthocephalus Macrophyllus (Roxb.) Havil)The supply of water to the seeds of red jabon can enhance plant growth. In this research studied the effect of watering frequency on growth jabon water red. This study was conducted in Greenhouse Silviculture Faculty of Agriculture, University of Sam Rarulangi which runs from August s / d in October 2012. The purpose of this study was to determine the intensity of a good watering the seedlings growth jabon red. This study used an experimental method completely randomized design (CRD) with 4 treatments and 6 replications. Treatment A Watering the first time (600 cc), B is watering 2 times (300 cc), C is watering 3 times (200 cc) and D is Watering 4 times (150 cc). Growing media used in this study are basic media such as soil, sand and chicken manure with a ratio of 7: 2: 1. The parameters measured were plant height, diameter, leaf number, root volume, dry crown weight, temperature and humidity.The results showed that there is an influence on the frequency of watering is water height growth, diameter, number of leaves, root volume and dry weight of seedlings jabon red canopy. Watering 2 times a day (300 cc), can provide good results in high growth, diameter, number of leaves and dry weight of the canopy. While the root volume parameter, watering 4 times a day (150 cc) gives good results.